2019
DOI: 10.1590/1980-5373-mr-2018-0639
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of a Silica-Alumina Membrane Using Novel Tubular Freeze-Cast Substrates

Abstract: Development of new ceramic membranes has recently grown due to its superior thermal and mechanical stability. An interesting approach to manufacture asymmetric membranes is the production of aligned pore structure by the freeze-casting method. The lack of studies involving membrane production with tubular freeze-cast substrates warrants more research. In this study, a novel tubular freeze-cast alumina substrate was used for deposition of a silica top layer. The substrate showed radially aligned pores, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The alumina freeze-cast tubes produced in this study have already been reported in previous studies describing the structure of the macropores produced by freeze-casting and its influence on the mechanical behavior 21,47 , as well as for production of membranes 14,57 . Representative micrographs of the radially aligned porosity are reproduced for reader's ease in Figure 1a, with pore sizes ranging within 5-10 µm 57 .…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The alumina freeze-cast tubes produced in this study have already been reported in previous studies describing the structure of the macropores produced by freeze-casting and its influence on the mechanical behavior 21,47 , as well as for production of membranes 14,57 . Representative micrographs of the radially aligned porosity are reproduced for reader's ease in Figure 1a, with pore sizes ranging within 5-10 µm 57 .…”
Section: Resultsmentioning
confidence: 85%
“…The alumina freeze-cast tubes produced in this study have already been reported in previous studies describing the structure of the macropores produced by freeze-casting and its influence on the mechanical behavior 21,47 , as well as for production of membranes 14,57 . Representative micrographs of the radially aligned porosity are reproduced for reader's ease in Figure 1a, with pore sizes ranging within 5-10 µm 57 . The microstructure exhibiting the grains after sintering is also reproduced in Figure 1b, c for each sintering temperature used in this study, with average grain sizes of 237±44 nm, 250±34 nm and 500±105 nm for the samples sintered at 1300 °C, 1400 °C and 1500 °C, respectively 21 .…”
Section: Resultsmentioning
confidence: 85%
“…The highly organized pore structure of the tubular freezecast substrates has already been discussed in other reports previously published and is only briefly reproduced in this study for reader's ease 17,26 . The substrates showed radially aligned pores with lamellar geometry (Figure 1a, b), typical of freeze-cast substrates produced from suspensions using water as solvent.…”
Section: Substrate Properties and Maximum Tensile Stressmentioning
confidence: 81%
“…The production method of the tubular substrates is already reported elsewhere 17,26 . In summary, ceramic suspensions were prepared with alumina concentrations varying within 10-30 vol%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation